Hubungan Kepemimpinan Transformasional Dan Efikasi Diri Dengan Organizational Citizenship Behavior (OCB) - Saepul Anwar; Muhamad Entang; Rais Hidayat (Universitas Pakuan, 2023)
THE CORRELATION BETWEEN TRANSFORMATIONAL LEADERSHIP AND SELF EFFICACY WITH ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB).This study aims to examine the correlation between transformational leadership and self-efficacy with OCB. The research was conducted at the Ciomas Korwil Private Vocational School in September 2020. The study population was 191 teachers and the sample size was 130 teachers using proportional random sampling. Collecting data for each variable studied using a questionnaire with a Likert scale. The analysis technique uses partial correlation and multiple correlation. The results showed that there was a positive relationship between transformational leadership and OCB (correlation coefficient ry1 = 0.551 and determination coefficient r2y1 = 0.134), there was a positive relationship between self-efficacy and OCB (correlation coefficient ry2 = 0.284 and coefficient of determination r2y2 = 0.080) and there was a positive relationship. and very significant between transformational leadership and self-efficacy together with OCB (correlation coefficient ry12 = 0.441 and coefficient of determination r2y12= 0.194). Thus, it can be concluded that OCB can be improved through transformational leadership and self-efficacy both partially and collectively.